1992
DOI: 10.1016/0378-1097(92)90060-2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant acellular pertussis vaccine — from the laboratory to the clinic: improving the quality of the immune response

Abstract: Vaccination is the most effective way to prevent infectious diseases. Recombinant DNA technologies have provided powerful new tools to develop vaccines that were previously impossible or difficult to make, and to improve the vaccines that were already available but had been developed using old technology. In the case of whooping cough, an effective vaccine (composed of killed bacterial cells) is available, but its use is controversial because of the many side effects that have been associated with it. An impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Bordetella pertussis is a Gram-negative bacterium that causes whooping cough in children. The surge of molecular biological research into the virulence and vaccinology of B. pertussis over the last few years has concentrated almost exclusively on proteins (Rappuoli et a/., 1992;Cherry, 1992) and little work has been done on non-protein structures that may be involved in the infectious process.…”
Section: Introductionmentioning
confidence: 99%
“…Bordetella pertussis is a Gram-negative bacterium that causes whooping cough in children. The surge of molecular biological research into the virulence and vaccinology of B. pertussis over the last few years has concentrated almost exclusively on proteins (Rappuoli et a/., 1992;Cherry, 1992) and little work has been done on non-protein structures that may be involved in the infectious process.…”
Section: Introductionmentioning
confidence: 99%
“…Bordetella bronchiseptica has only rarely been associated with human disease (13,34,42) and is more commonly known as a pathogen of a range of species, including rabbits, pigs, dogs, and cats, among others (1,5,17,23,35,43,44,49). In the search for improved modern vaccines directed against B. pertussis, a large body of work has been generated regarding protein virulence factors and targets for protective immunity (8,32). This has led to a relative lack of research into the lipopolysaccharide (LPS) molecule found on the bordetellae, which is highly biologically active as an endotoxin, an immunomodulator, and an antigen (3,7,48).…”
mentioning
confidence: 99%
“…Parenterally administered PTX can potentiate IgE and delayed-type hypersensitivity to coadministered proteins (23,41). PTX is one of the major protective antigens of B. pertussis, and inactivated forms of PTX form the basis of currently used and experimental acellular pertussis vaccines (31). A genetically detoxified form of PTX (PT-9K/129G) which lacks the deleterious properties of PTX but which can still bind to eucaryotic cells and is highly immunogenic in rodents and humans has been constructed (24,28,29,31).…”
mentioning
confidence: 99%